STEM MOTH (Ostrinia nubilalis Hbn.) AND ITS HARMFULNESS ON THE COMMERCIAL CROPS OF MODERN CORN HYBRIDS - Колесников, Л. О.; Васильев, А. А. (Scientific Progress & Innovations, 2017)
Corn stem moth (Ostrinia nubilalis Hbn.) is one of the most economically important pests of corn crops now. It’s the reason of the loss of 4–25 % of the crop according to different published sources. The seed producers are advised to use resistant against stem moth of corn hybrids. Resistance involves an assessment of the hybrids toughness to the stems breakage (direct losses) and to the reduction of productivity (hidden losses). Resistance of modern hybrids to the stems breakage is high enough, so in 2015–2016, on the territory of Central Ukraine studies have been conducted concerning the reduction of productivity of corn plants damaged by caterpillars of the stem moth. The research was conducted on commercial corn crops in Poltava region. The population of stem moth was on the 18,6–56 % of crops, and yield losses from stem moth damage was 4,9–19,2 kg/ha.